The Srebrenica genocide: lest we forget - Omer, Spahic (Islamicity.org, 2019)
The Srebrenica genocide (genocid u Srebrenici), or massacre (masakr), was a massacre of more than 8,000 Bosniaks (Bosnian Muslims), especially men and boys, in the city of Srebrenica in the easternmost part of Bosnia and Herzegovina near the border with Serbia. The tragedy took place in July 1995. The genocide was the culmination of Serb aggression against the independent and sovereign state of Bosnia and Herzegovina. The aggression started in April 1992 and ended in December 1995. The genocide was committed by the Bosnian Serb Army of Republika Srpska (then a quasi and utterly illegal entity inside Bosnia and Herzegovina), with the help of various military and paramilitary units from the neighboring Serbia. The Army was under the command of Ratko Mladić. Republika Srpska was under the political, as well as ideological, leadership of Radovan Karadžić, who was under the complete tutelage of Serbia and its leader, Slobodan Milošević. Apart from the killings, more than 20,000 civilians were also expelled from the Srebrenica enclave as part of the process of ethnic cleansing. The people were deported and forcibly displaced – not only from Srebrenica, but also from many other Bosnian cities and villages – in order to create vast homogenous Serb geographical areas. The areas were meant to subsequently become part of a Greater Serbia.